Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/19417381211014487
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction and Lateral Plasty in High-Risk Young Adolescents: Revisions, Subjective Evaluation, and the Role of Surgical Timing on Meniscal Preservation

Abstract: Background: In adolescents, the rate of meniscal injury at the time of anterior cruciate ligament (ACL) reconstruction, the rate of ACL graft revision, and clinical outcomes has not yet been investigated. Hypothesis: In patients younger than 16 years, the rate of meniscal injuries at the time of ACL reconstruction increases with time from injury. The mid-term revision rate and reoperation rate after ACL reconstruction with hamstrings and lateral tenodesis are lower than those reported in literature for isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A recent report evaluated the outcome of 151 patients younger than 16 years (mean age 14.8 years) showing a revision rate of only 6% and good or excellent Lysholm score was reported in 88% of the cases. Moreover, 91% of them returned to sport and 80% of them were still active at the final follow-up of 6 years [ 49 ]. Similarly, another report of 54 adolescents at a minimum follow-up of 10 years showed that those positive clinical results are stable over time with only 3.5% of revision rate and an average Lysholm of 95 points [ 50 ].…”
Section: Combined Procedures and Special Populationsmentioning
confidence: 99%
“…A recent report evaluated the outcome of 151 patients younger than 16 years (mean age 14.8 years) showing a revision rate of only 6% and good or excellent Lysholm score was reported in 88% of the cases. Moreover, 91% of them returned to sport and 80% of them were still active at the final follow-up of 6 years [ 49 ]. Similarly, another report of 54 adolescents at a minimum follow-up of 10 years showed that those positive clinical results are stable over time with only 3.5% of revision rate and an average Lysholm of 95 points [ 50 ].…”
Section: Combined Procedures and Special Populationsmentioning
confidence: 99%
“…Thankfully progress is being made, as evidenced in this issue of Sports Health. [4][5][6][9][10][11] Addressing the addition of ALL-like procedure (lateral tenodesis), Dr Alberto Grassi 5 emphasizes its use in high-risk young adolescents. With a follow-up of at least 2 years, only 6% of their hamstring ACL reconstructions augmented with lateral tenodesis underwent revision.…”
mentioning
confidence: 99%